Condylomata acuminata/Irsuties papillarum penis. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2002)
Condylomata acuminata in children are characterized by peculiar problems, regarding their causal factors, diagnosis and treatment. From a diagnostic point of view, condylomata acuminata should be differentiated from a physiological condition, the so called “irsuties papillarum penis”. On the other hand, condylomata acuminata can be easily differentiated from flat condylomata of syphilis, because the two disorders only share the site involved. Irsuties papillarum penis, which is well known by dermatologists, gets evident in the peripuberal period. It is responsible for significant psychological troubles in the teenage, when adolescents are particularly sensitive to the genital problems.